Extended-Spectrum Beta-Lactamase Producing Escherichia coli and Klebsiella pneumoniae are Emerging as Major Pathogens Responsible for Urinary Tract Infection - Iqbal, Sarwar; Rahim, Muhammad Abdur; Samad, Tabassum; Ananna, Mehruba Alam; Mitra, Palash; Chowdhury, Tufayel Ahmed (Bangladesh Critical Care Journal, 2015)
Background: Escherichia coli and Klebsiella pneumoniae are two common organisms responsible for urinary tract infection (UTI) world-wide. Extended-spectrum beta-lactamase (ESBL) producing E. coli and K. pneumoniae are increasingly being reported as urinary isolates. Objectives: This study was aimed to describe the frequency of ESBL positive E. coli and K. pneumoniae causing UTI, associated risk factors and antibiotic sensitivity pattern of these organisms. Methods: This prospective cross-sectional study was conducted in BIRDEM General Hospital from January 2014 to March 2014. One hundred consecutive culture positive UTI cases due to E. coli or K. pneumoniae infection, irrespective of ESBL positivity were purposively included in this study. UTI due to organisms other than E. coli and K. pneumoniae and culture negative cases were excluded from the study. Results: Total patients were 100, male were 21 and female 79. Mean age was 59.1 (range 19-81) years. Out of 100 patients, 96 were diabetic. Fever, vomiting, dysuria and increased urinary frequency were common symptoms. Among the 100 culture positive samples, E. coli were 84 and K. pneumoniae were 16. Forty eight (48/84, 57.1%) of E. coli and 10 (10/16, 62.5%) of K. pneumoniae were ESBL positive. Female patients, presence of diabetes mellitus (DM), long duration and poor control of DM, chronic kidney disease (CKD), renal stone and past history of UTI were significant risk factors for ESBL positivity. Amikacin, netilmycin and imipenem were among the most sensitive antibiotics. Conclusion: Two-thirds of the E. coli and K. pneumoniae in this study were ESBL positive. Female gender with poor control of DM, CKD and past history of UTI were significant risk factors for ESBL positivity. Aminoglycosides and carbapenems remain the drug of choice. Bangladesh Crit Care J September 2015; 3 (2): 49-52